Traffic alert for Aug. 29 football game - Uribes, Tom::::::::: (2013)
With Fresno States season opening football game at Bulldog Stadium falling on Thursday, Aug. 29. (aweek night when classes are in session), motorists around the campus are advised to plan aheadfor traffic congestion and parking lot closure or impact